Modified volumetric modulated arc therapy technique with reduced planning and treatment time for craniospinal irradiation utilising two isocentres. Issue 3 (22nd April 2022) - Nguyen, Minh; Dang, Thu; Deegan, Liz; Henry, Kelsie; Jones, Scott; Pullar, Andrew; Cheuk, Robyn; Gibbs, Adrian; Sim, Lucy; Hargrave, Catriona
Abstract: Introduction: Paediatric patients (individuals below 18 years of age) requiring cranial‐spinal irradiation (CSI) at our institution are commonly planned and treated using a three isocentre (3‐ISO) volumetric modulated arc therapy (VMAT) technique. A modified two isocentre (2‐ISO) VMAT technique was investigated with the aim to improve workflow and reduce planning and treatment time. Methods: Five CSI paediatric patients previously treated with a 3‐ISO VMAT technique were retrospectively replanned using a 2‐ISO VMAT technique. The 2‐ISO VMAT plans were reviewed and approved by a radiation oncologist (RO) before undergoing patient‐specific quality assurance (QA) procedures, performed by a radiation oncology medical physicist (ROMP). Planning target volume (PTV) coverage, organ‐at‐risk (OAR) dose as well as planning and treatment durations of the first five patients utilising 2‐ISO technique were compared with 3‐ISO technique. Results: The average percentage difference in PTV coverage by 95% reference dose between the 2‐ISO and 3‐ISO is 0.14%, and the average difference in OAR median dose is 0.68 Gy. Conformity and homogeneity indices have the same averages at 1.18 and 0.4 respectively. Patient‐specific physics QA results were all comparable with the 3‐ISO averages at 98.84% and the 2‐ISO at 98.71%. Planning duration for the 2‐ISO was reduced by up to 75%, and daily treatment duration was reduced by up to 50%. Of all the previously treated CSI patients using a 3‐ISO technique, 45% were suitable for the 2‐ISO technique. Conclusion: The 2‐ISO VMAT technique provided comparable dose distribution based on PTV coverage, OAR dose and plan metric indices. Reduced planning and treatment duration with the 2‐ISO technique facilitated improved workflow with decreased sedation time for paediatric patients requiring a general anaesthesia. Abstract : A modified two isocentre (2‐ISO) volumetric modulated arc therapy (VMAT) technique was investigated to determine whether it was dosimetrically equivalent to a 3‐ISO VMAT technique and whether it can provide for an improved workflow process for planning and treatment of CSI patients. The new 2‐ISO VMAT technique provided comparable dose distribution and patient‐specific QA results to the 3‐ISO technique. Its reduced planning and treatment times allows patients to commence treatment earlier, reduces sedation time during treatment if it is required and assists with limiting intra‐fraction motion while potentially increasing treatment accuracy.